2001
DOI: 10.1088/0741-3335/43/9/305
|View full text |Cite
|
Sign up to set email alerts
|

Observation of parametric decay instability during ion Bernstein wave heating experiments on HT-7

Abstract: The parametric decay processes with a power threshold of 70 kW have been observed on the HT-7 tokamak. Two types of parametric decay instabilities have been identified. The pump wave decays into an ion cyclotron quasi-mode and an ion Bernstein wave, or decays into a low-frequency electron Landau damped quasi-mode and an ion Bernstein wave. The experimental observation shows good agreement with theoretical prediction. Other peaks at a frequency of n D are also observed. The main features of the observed radiofr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…We consider an inhomogeneous plasma with both density and magnetic field varying with the radial position. The simulation parameters have been chosen to resemble those of the IBW experiments on the HT-7 tokamak [17]. In the simulations, we obtain resonant and nonresonant parametric decay channels similar to those observed in the experiments.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…We consider an inhomogeneous plasma with both density and magnetic field varying with the radial position. The simulation parameters have been chosen to resemble those of the IBW experiments on the HT-7 tokamak [17]. In the simulations, we obtain resonant and nonresonant parametric decay channels similar to those observed in the experiments.…”
Section: Introductionmentioning
confidence: 95%
“…With more and more applications of rf waves for plasma heating and current drive on tokamak devices, the interactions between waves and plasmas have been investigated extensively [9][10][11][12][13][14][15][16][17][18]. When the input power of the incident wave reaches a megawatt, nonlinear phenomena occur and cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reveal these effects in relevant experiments, we choose the plasma parameters close to those of the ion Bernstein wave (IBW) heating experiments on HT-7 tokamak. [1,14] It is demonstrated that more decay channels appear and the frequency spectra broaden as the input power is increased. The characteristics of the spectral broadening and how this broadening comes out will be presented.…”
mentioning
confidence: 99%